Development of natural science supplement books based on local wisdom in integrative thematic learning in the elementary schools - Ifan Anom Bintoro Aji; Pratiwi Pujiastuti (Jurnal Prima Edukasia, 2022)
The purpose of this study was to develop a natural science supplement book based on local wisdom in thematic-integrative learning in the fourth grade of elementary schools. This study uses Research and Development of the Dick and Carey model. The research data were obtained through observation, interviews, and questionnaires. The results of the feasibility of a local wisdom-based science supplement book were obtained through a product assessment questionnaire for material experts, media experts, linguists, and classroom teachers. While the trial results were obtained through a response questionnaire given to 58 fourth-grade elementary school students. The results of the validators show that the science supplement book is very feasible from the assessment of the material aspects with an average of 86.33%, the media aspect is also considered very feasible with an average of 91.63%, while the language aspect is considered feasible with an average of 76.67%. The results obtained from practitioners also get very feasible criteria with an average of 87.06%. The results of small-scale trials obtained an average of 100% and the results of large-scale trials obtained an average of 97,08% with very good criteria. Based on these results, the local wisdom-based science supplement book is very suitable for fourth-grade elementary school teachers in thematic-integrative learning.